Toxic Reactions in Probable and Confirmed Methotrexate Overdose in Rheumatology Patients: A Case Series - S. A. Doktorova; I. V. Andreeva; D. G. Krechikova; Yu. Yu. Grabovetskaya; O. S. Mazhaeva; V. V. Rafalskiy (Безопасность и риск фармакотерапии)
INTRODUCTION. Low-dose methotrexate (less than 30 mg/week) is the standard therapy for rheumatic diseases. Methotrexate overdose due to errors by patients or medical staff may lead to severe complications and life-threatening conditions.CASE DESCRIPTION. This article presents a retrospective analysis of the medical records of three clinical cases of methotrexate overdose with toxic reactions (one probable and two confirmed cases) observed in rheumatology patients at general and preventive medicine clinics in the Kaliningrad and Smolensk regions in 2019–2024. The analysis examined the clinical presentation of methotrexate overdose, medical history, concomitant therapy, laboratory findings, and patient management strategy from the time of admission. All patients had confirmed rheumatic diagnoses, including psoriatic arthritis (one male, 59 years old) and seropositive rheumatoid arthritis (two females, 68 and 57 years old). As a baseline anti-inflammatory therapy, patients received methotrexate at a dose of 10–20 mg/week with the mandatory addition of folic acid at a dose of at least 5 mg/week. Patients had concomitant renal, cardiovascular, and metabolic disorders. The primary cause of these overdose cases was that the doses prescribed for weekly administration were taken daily. Overdose manifested as haemorrhagic syndrome, erosive and ulcerative mucosal lesions, dyspepsia, and changes in laboratory findings. In two confirmed overdose cases, adverse drug reactions manifested 13 and 14 days after the start of erroneous methotrexate administration. Two patients died on days 4 and 7 from admission, and one patient recovered and was discharged after 40 days of hospital stay.CONCLUSIONS. Methotrexate overdose can lead to haematopoietic, gastrointestinal, cutaneous, and mucosal disorders and result in life-threatening conditions and even death. The described cases emphasise the importance of clearly informing patients of methotrexate dosing regimens and possible symptoms of overdose. This approach can mitigate the potential risk and adverse consequences of overdose while improving the safety of outpatient methotrexate treatment for rheumatic diseases.